Pelatihan Pembuatan Pupuk Organik dengan Metode Ember Tumpuk Untuk Budidaya Tanaman Karangkitri di Desa - Noer Af'idah; Andri Wahyu Wijayadi; Nur Hayati; Lina Arifah Fitriyah; Roudhoutul Aulia Rochim (I-Com: Indonesian Community Journal, 2024)
This activity aims to improve the welfare of the Randuwatang Village community through training in making organic fertilizer using the stacked bucket method for cultivating coral reef plants. It is known that Randuwatang Village only has a TPS 3R waste bank, but the management team and community are not yet skilled at processing waste into more useful products. On the other hand, the community is starting to abandon the cultivation of coral reef plants which use the yard area around the house. Making organic fertilizer using the stacked bucket method is a composter process that is very suitable for managing organic waste on a household scale. The method used in this service is education on waste processing and coral cultivation, as well as a practical demonstration of making organic fertilizer using the stacked bucket method. The results of this service were in the form of participant participation reaching 100%, participants' activeness and understanding of the material reaching 88%, and 85% of participants being skilled in making organic fertilizer using the stacked bucket method.